A Perspective on Conflict and Performance of International Construction Projects - Al-Sibai, *Eyad Zouher; Alashwal, Ali Mohammed (Journal of Surveying, Construction and Property, 2014)
Conflict is unavoidable in any construction project and may influence its performance. International construction projects involve people from different backgrounds, professions, and ethnic groups. This milieu may become a trigger for sever conflict. The purpose of this paper is to highlight the influence of conflict on the performance of international construction projects. Conflict and project performance were measured using several variables synthesized from the relevant literature. Conflict variables were categorized into two types: internal and external conflicts. Subsequently, a questionnaire survey was developed and sent to individuals working in Malaysian contractor companies, who have experience in overseas projects. All together, 161 questionnaires were collected. Data analysis using linear regression indicated the influence of four variables of the internal conflict on project performance. It is evident that the external conflict may not be significant in the context of international construction project. Thus, it is important to pay greater attention to the internal-related variables of conflict to enhance project performance.